COMPARISON ANALYSIS OF LABOR PRODUCTIVITY AND CONSUMPTION - Кліпа, Іван (Socio-economic relations in the digital society, 2019)
The article attempts to formulate and solve the following problem: what is the nature of the relationship between accumulation and consumption for a long-term period, what is the experience of other states? As a result of the analysis it was revealed that for each given period of time, there is the following relationship between consumption and accumulation: (1) high growth rates are possible at relatively low growth rates of consumption, but decrease when consumption grows faster than the economy; (2) during periods of economic decline, the correlation between consumption and economic growth is strengthened, and during the economic growth this correlation is getting week.
Keywords: final consumption of households; social standards; social justice; economic growth